Fenomenologia e neurociência: uma relação possível - Martins, João Paulo [UNESP] (2015)
The present study aims to elucidate and understand the role of phenomenology in the context of neuroscience, in particular, whether and how the former has and can contribute to the development of the latter. The phenomenological perspective refers to a tradition of philosophy that originated in Europe by the philosopher Edmund Husserl and later followed with thinkers such as Martin Heidegger, Maurice Merleau-Ponty, Jean-Paul Sartre and contemporary thinkers, among them, Shaun Gallagher, Dan Zahavi and Evan Thompson, whose ideas will be the guiding thread of this dissertation. Currently phenomenology that is scoped to the study of the phenomenon, ie, that which presents itself to consciousness has been used as a methodology in neuroscience so that we can ratify the polls in the third person through a first-person approach, designing experiments proper and reasonable manner and for the interpretation of results obtained by empirical research. In this context, each with its goal, raises some theoretical lines that use of phenomenology and integrate what is regarded as the naturalization of phenomenology, taking as examples the neurophenomenology, the front-loading phenomenology and the mathematization of phenomenology. The status of naturalization of phenomenology is something corroborated by some thinkers who advocate for the advancement of scientific progress through various ways such as also seen antagonistically because flees the way in which phenomenology was proposed, to address science as a method of knowledge of what is strictly experienced by an experience subject.